The Effect of Quality, Service, Time and Price on Customer Satisfaction In The Welding and Construction Services Industry Lala Modern Workshop at Ruteng Flores, NTT - Febi Hermanto; Ach Faisol; Kartini (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of quality, service, time, and price factors on customer satisfaction in the welding and construction services industry at LALA Modern Workshop, Ruteng, Flores, NTT. The background of this research is based on the phenomenon of increasing public needs for infrastructure and property, as well as high customer expectations for service quality, punctuality, and transparent prices. The analysis technique used is multiple linear regression analysis with SPSS, to identify the direct relationship between independent variables (quality, service, time, and price) and dependent variables (customer satisfaction). The results show that quality, service, time, and price significantly affect customer satisfaction, with quality and service as the dominant variables. In addition, this study also shows that punctuality and appropriate pricing make an important contribution in shaping a positive customer experience. This research provides theoretical benefits in the development of academic literature related to customer satisfaction in the construction and welding services sector, as well as practical benefits in the form of strategic recommendations for LALA Modern Workshop to improve their business performance. Thus, the results of the research are expected to be the foundation for companies in developing more effective strategies and increasing their competitiveness in a competitive market.